Global stiffness and residual stresses in spinal fixator systems: A validated finite element study on the interconnection mechanism. (November 2022) - Ciriello, Luca; Berti, Francesca; La Barbera, Luigi; Villa, Tomaso; Pennati, Giancarlo
Abstract: Posterior spinal fixation systems are the gold standard to treat different column disorders using rods and screws. The proper connection between them is guaranteed by the Interconnection Mechanism (IM), consisting of different metallic subcomponents held together through the application of tightening torque. The response of the fixation system is defined by its overall stiffness, which in turn is governed by the local residual stress field arising during tightening. Although literature computational models for studying spinal fixation are becoming increasingly anatomically complex, most studies disregard completely the realistic modeling of the IM, namely choosing elastic-plastic material models and proper contact interactions. In this frame, the present study aims at increasing awareness in the field of spinal fixation modeling by investigating the mechanical response of the IM in terms of overall stiffness and local residual stresses. Once validated through dedicated experiments, the results of the proposed model have been compared with the current literature, highlighting the key role of the IM in the reliable modeling of spinal fixation. Graphical abstract: Image 1 Highlights: The tightening of the IM allows for the stability of spinal fixators. Currently, IM models are oversimplified in the material and interaction properties. Elastic-plastic material properties are mandatory for the evaluation of residuals. The global stiffness is ruled by the interactions among the subcomponents of the IM. Dedicated experimental allowed the validation of the IM finite element model.